Intratumoral FoxP3+Helios+ Regulatory T Cells Upregulating Immunosuppressive Molecules Are Expanded in Human Colorectal Cancer - Syed Khaja, Azharuddin Sajid; Toor, Salman M.; El Salhat, Haytham; Ali, Bassam R.; Elkord, Eyad (Frontiers in Immunology, 2017)
Regulatory T cells (Tregs) can be anti-tumorigenic or pro-tumorigenic in colorectal cancer (CRC) depending on the presence of different Treg subsets with various immunosuppressive molecules. Some studies reported the phenotypic characteristics of tumor-infiltrating immune cells in CRC but limited studies have focused on the co-expression of suppressive molecules on immune cells. The aim of this study was to characterize immune cells in the tumor microenvironment (TME), compared to paired adjacent non-tumor colon tissue of CRC patients. Additionally, we investigated co-expression of immunosuppressive molecules on different Treg subsets in the TME, normal colon tissue and peripheral blood of CRC patients and healthy donors. In this preliminary study, we report that the majority of CD3+ T cells in the TME are CD4+ cells with high co-expression of PD-1/CTLA-4 and PD-1/CD39 molecules. Levels of CD4+FoxP3+Helios+ Tregs were significantly increased in the TME. Furthermore, we observed increased levels of PD-1/CTLA-4 and PD-1/CD39 co-expressing cells within FoxP3+Helios+ and FoxP3+Helios- Treg subsets, indicative of their potent immunosuppressive potential. These results suggest synergistic associations between PD-1/CTLA-4 and PD-1/CD39 in dampening T-cell activation and function along with suppressing tumor-specific immune responses, suggesting that dual blockade of these molecules could be a more effective strategy for inducing anti-tumor immune responses in CRC.